2021
DOI: 10.3389/fpsyt.2021.647483
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Level During the Second Localized COVID-19 Pandemic Among Quarantined Infertile Women: A Cross-Sectional Survey in China

Abstract: Infertility usually causes mental health problems for patients and unfavorable emotions such as anxiety and depression can have an adverse effect on women's normal pregnancy. We aimed to compare the anxiety level between infertile female patients in quarantined and non-quarantined areas during the second wave of COVID-19 epidemic. A total of 759 infertile women were included in this cross-sectional study conducted through an online survey. Anxiety was measured by the State-Trait Anxiety Inventory (STAI) tool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
2
9
0
5
Order By: Relevance
“…Anxiety scores were higher in women who underwent IVF than in women who did not undergo IVF ( P = 0.007). [ 26 ] The effects of cancellation of the couple's infertility treatment cycle were observed in the form of mood disorders, anxiety, sleep disorders, and depressive symptoms. [ 27 ] The mental health scores of participants in the COVID-19 disease control period were lower than those in the outbreak period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety scores were higher in women who underwent IVF than in women who did not undergo IVF ( P = 0.007). [ 26 ] The effects of cancellation of the couple's infertility treatment cycle were observed in the form of mood disorders, anxiety, sleep disorders, and depressive symptoms. [ 27 ] The mental health scores of participants in the COVID-19 disease control period were lower than those in the outbreak period.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 24 ] Furthermore, infertile couples think that they themselves have no control over the infertility treatment process and this is emotionally damaging them, they will feel helpless if treatment is suspended, which is directly related to depression and anxiety. [ 24 26 ] Women who had been trying to conceive for a longer time reported a greater negative mental health effect of treatment suspensions. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, numerous studies have examined women with infertility (Table 3 ). Ceasing infertility treatment was the primary problem affecting patients [ 27 , 41 , 42 ], while changes in working environment and style [ 43 ], quarantine [ 44 ], and financial concerns [ 45 ] increase the psychological burden of patients. Negative emotions were found to reduce the quality of couples’ relationships [ 28 ] and lower expectations of future pregnancy [ 46 ] during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that subfertile women have more depression and anxiety, and this may negatively affect their conception 20 . Cao et al 9 reported that women who were in the home quarantine had more anxiety, and women with a longer infertility duration were more likely to have anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lablanche et al 8 found that during the COVID‐19 pandemic, subfertile women had more perceived stress compared to anxiety and depression (27 ± 6.75 vs. 7.58 ± 3.85 and 4.51 ± 3.48, respectively). Also, Cao et al 9 reported that the rate of anxiety among women who were in home quarantine was significantly more than that in subfertile women without home quarantine. Another study revealed that the infertility treatment of most subfertile women was stopped or postponed during COVID‐19 pandemic and this may be the cause for stress and anxiety, especially among older patients (older than 35 years old) 10 .…”
Section: Introductionmentioning
confidence: 99%